Terrestrial Passive Acoustic Monitoring: Review and Perspectives - Moreira Sugai, Larissa Sayuri [UNESP]; Freire Silva, Thiago Sanna [UNESP]; Ribeiro, Jose Wagner [UNESP]; Llusia, Diego (Oxford Univ Press, 2019)
Passive acoustic monitoring (PAM) is quickly gaining ground in ecological research, following global trends toward automated data collection and big data. Using unattended sound recording, PAM provides tools for long-term and cost-effective biodiversity monitoring. Still, the extent of the potential of this emerging method in terrestrial ecology is unknown. To quantify its application and guide future studies, we conducted a systematic review of terrestrial PAM, covering 460 articles published in 122 journals (1992-2018). During this period, PAM-related studies showed above a fifteenfold rise in publication and covered three developing phases: establishment, expansion, and consolidation. Overall, the research was mostly focused on bats (50%), occurred in northern temperate regions (65%), addressed activity patterns (25%), recorded at night (37%), used nonprogrammable recorders (61%), and performed manual acoustic analysis (58%), although their applications continue to diversify. The future agenda should include addressing the development of standardized procedures, automated analysis, and global initiatives to expand PAM to multiple taxa and regions.
Keywords: audio recorders; auditory monitoring; automated data collection; bioacoustics; ecoacoustics; faunal survey; soundscapes